JOINT AND DIRECT EFFECTS OF GENOTYPES AND ENVIRONMENT CONDITIONS ON YIELD OF HYBRID MAIZE SEED - Tabakovic, Marijenka (Journal on Processing and Energy in Agriculture, 2022)
This study aimed to evaluate the influence of environmental conditions and genotype on the yield of three maize lines and the morphological properties of cobs and seeds. Three hybrid maize lines were used as material in the study, two years (2019-2018) and one location (Zemun Polje). The following parameters were monitored: 1000-seed weight, seed volume, bulk density, cob length, cob thickness, fraction content and grain yield. The average grain yield for all three lines in the first and the second year was 6.13 t ha-1 and 4.66 t ha-1, respectively. A significant impact of environment was noticed on 1000 seed weights in both years (2018 and 2019), 327.56 g and 251.77 g, respectively. In 2018 proportion of small fraction and large fractionSF/KF was 18.47/78.49% (p≤0.05). In the second year, SF/KF relation , was 45.15/40.08%. Qualitative dependence of yield and morphological characteristics of cobs and seeds, which expressed through the coefficient of determination was R2 0.514. All morphological characteristics of seeds significantly correlated each with other (p≤0.01, p≤0.05). Monitoring and analysis of weather changes at the local level, includingf air and soil temperature conditions, as well as precipitation, are crucial for the establishment of new systems of cropping practices.